Energy recovery in water supply systems using hydroturbines - Koçak, Eyup (2018)
In the last century, the main source of hydroelectric power came from conventional dams and the energy produced by hydro turbines had a fast growing. New applications of turbines in hydro power even in micro-scale projects have emerged. Water supply systems are large energy consumers due to the large amount of energy needed for pumping the water from low to high heights. However, gravity fed subsystems generally presents excess of pressure, which is lost with pressure reducing valves. Therefore, energy can be recovered from locals of excessively high flow and pressure. Nevertheless, water networks are highly complex systems and the flow conditions change instantaneously throughout the network. The control of the pressure is the top priority of the system providers and energy should be converted along with keeping the pressure to a desired level. The application of turbines appeared as an alternative to produce energy, to reduce leakage reductions and to manage network pressure. This work aims to investigate the energy production in water supply systems using micro hydro turbines. To find the optimal location for the installation of micro hydro turbine in the network, a tool is developed using the hydraulic simulator EPANET for obtaining flow regimes of each pipe. Technical feasibility analysis is automatically computed for the selection of appropriate type turbine and the CFD program ANSYS is used to design and verify the hydraulic performance of the turbine. A financial analysis is performed and has showed that energy production in water supply systems using micro turbines is a profitable alternative and a renewable solution for the world’s growing energy needs.